ApoBDs: a paradigm shift from cellular debris to therapeutic vehicles - Xiong, Zixuan; Xiao, Fen; Sun, Yuanyuan; Su, Hankun; Liu, Di; Tang, Boya; Jian, Wenyan; Yang, Tianli; Zhao, Jing; Li, Yanping; Li, Hui (Frontiers in Endocrinology, 2025)
Apoptosis, a genetically programmed cell death process, is essential for maintaining tissue homeostasis. Apoptotic vesicles (ApoVs), membrane-bound vesicles generated during apoptosis and once considered mere cellular debris, can be classified into apoptotic bodies (ApoBDs), microvesicles, and apoptotic extracellular vesicles (ApoEVs) based on their grain size. These vesicles, packed with bioactive molecules, not only drive tumor growth and metastasis, but also contribute to tissue and organ repair. This review focus on the origins, formation mechanisms, and dual functions of ApoBDs across various diseases, highlighting their paradoxical nature as both disease promoters and therapeutic allies. It further explores the application prospects and clinical practice of ApoBDs in cancer treatment, immune modulation, and tissue regeneration. Additionally, we provide a comprehensive perspective on the transformative potential of ApoBDs in modern medicine, while outlining current challenges and future directions for ongoing research and clinical application.